\(\sqrt{x+2=\frac{5}{7}}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 1 2018

b, Đk : x >= -2

pt <=> x+2 = 25/49

<=> x = 25/49 - 2 = -73/49

Tk mk nha

1 tháng 12 2019

a) \(\sqrt{16}x+\frac{3}{4}=2\sqrt{\frac{4}{25}}+0,01.\sqrt{100}\)

=> \(4x+\frac{3}{4}=2\cdot\frac{2}{5}+0,01\cdot10\)

=> \(4x+\frac{3}{4}=\frac{4}{5}+0,1\)

=> \(4x+\frac{3}{4}=0,9\)

=> \(4x=0,9-\frac{3}{4}\)

=> \(4x=0,15\)

=> \(x=0,15:4=0,0375\)

b) \(\left(x-\frac{2}{5}\right)\left(x+\frac{3}{7}\right)=0\)

=> \(\orbr{\begin{cases}x-\frac{2}{5}=0\\x+\frac{3}{7}=0\end{cases}}\)

=> \(\orbr{\begin{cases}x=\frac{2}{5}\\x=-\frac{3}{7}\end{cases}}\)

11 tháng 2 2018

a,\(\frac{25x}{3}=\frac{\frac{4}{7}}{\frac{2}{7}}=7\)=> x=\(\frac{21}{25}\)

b,\(\frac{0,15}{3\sqrt{x}}=\frac{0,3\cdot3}{2}\)<=>\(0,3=0,3\cdot9\sqrt{x}\)Hay \(\sqrt{x}=\frac{1}{9}=>x=\frac{1}{3}\)

22 tháng 7 2019

\(a,\sqrt{x}=7\left(ĐKXĐ:x\ge0\right)\) 

    \(\Leftrightarrow\) \(\sqrt{x}=\sqrt{49}\)

    \(\Leftrightarrow\) \(x=49\) 

  Kết hợp với ĐK  x >= 0 \(\Rightarrow\)  x=49 (t/m )

  vậy x=49

\(\)

     

22 tháng 7 2019

\(b,\sqrt{x+1}=11\left(ĐKXĐ:x\ge-1\right)\)

  \(\Leftrightarrow\sqrt{x+1}\) =    \(\sqrt{121}\) 

   \(\Leftrightarrow\) \(x+1=121\) 

   \(\Leftrightarrow\) \(x=120\) kết hợp với ĐK x >= -1 \(\Rightarrow\) x=120 ( t/m )

  Vậy x=120

8 tháng 7 2018

1) \(\frac{x-1}{3}=\frac{5-x}{7}\Leftrightarrow7.\left(x-1\right)=3.\left(5-x\right)\)

\(\Leftrightarrow7x-7=15-3x\)

\(\Leftrightarrow7x+3x=15+7\)

\(\Leftrightarrow10x=22\)

\(\Leftrightarrow x=\frac{11}{5}\)

2) \(\frac{x-1}{-5}=\frac{-20}{x-1}\)

\(\Leftrightarrow\left(x-1\right)^2=\left(-20\right).\left(-5\right)=100\)

\(\Leftrightarrow100=\orbr{\begin{cases}10^2\\\left(-10\right)^2\end{cases}}\)

Nếu  x - 1 = 10 => x = 11

Nếu x - 1 = -10 => x = -9

Vậy ....

3) \(3\sqrt{x-3}+5=\left|-8\right|\)

\(\Leftrightarrow3\sqrt{x-3}+5=8\)

\(\Leftrightarrow3\sqrt{x-3}=3\)

\(\Leftrightarrow\sqrt{x-3}=1\) (ĐK: \(x\ge3\))

\(\Leftrightarrow\left(\sqrt{x-3}\right)^2=1^2\)

\(\Leftrightarrow x-3=1\)

\(\Leftrightarrow x=4\) (nhận)

Vậy x = 4

17 tháng 11 2016

\(\sqrt{x+2}\) = \(\frac{5}{7}\)

\(\Rightarrow\) x + 2 = \(\left(\frac{5}{7}\right)^2\)

\(\Rightarrow\) x + 2 = \(\frac{25}{49}\)

\(\Rightarrow\) x = \(\frac{25}{49}\) - 2

\(\Rightarrow\) x = \(\frac{-73}{49}\)

Vậy x = \(\frac{-73}{49}\)

17 tháng 11 2016

\(\sqrt{x+2}=\frac{5}{7}\)

\(\Rightarrow x+2=\left(\frac{5}{7}\right)^2\)

\(\Rightarrow x+2=\frac{25}{49}\)

\(x=\frac{25}{49}-2=-\frac{73}{49}\)